Metabolic reprogramming by pseudorabies virus: nucleotide metabolism as a central vulnerability for viral replication and pathogenesis - Chen, Xiaoyong; Wang, Qingsen; Chen, Xi (Frontiers in Microbiology, 2025)
Pseudorabies virus (PRV), a neurotropic alphaherpesvirus, causes severe neurological and reproductive disorders in swine, posing substantial threats to the global swine industry and emerging as a zoonotic concern. Viral metabolic reprogramming is a conserved strategy to support replication, yet the metabolic landscape of PRV infection remains incompletely defined. Here, we employed ultrahigh-performance liquid chromatography-mass spectrometry (UPLC–MS)-based metabolomics combined with multivariate statistical analysis to systematically profile metabolic changes in PRV-infected porcine kidney PK-15 cells. Unsupervised principal component analysis (PCA) and supervised orthogonal partial least squares-discriminant analysis (OPLS-DA) revealed a striking separation of metabolic phenotypes between PRV-infected (48 hpi) and control (0 hpi) cells, with the first principal component accounting for >73% of total variance, confirming significant metabolic reprogramming upon infection. We identified 1,634 and 925 differential metabolites in ESI+ and ESI− modes, respectively, with hierarchical cluster analysis revealing distinct signatures: amino acids and heterocyclic compounds were predominantly upregulated, while glycerophospholipids (GPs) were markedly downregulated. KEGG pathway enrichment analysis highlighted key perturbed networks underlying PRV pathogenesis: glycerophospholipid metabolism was targeted to modulate membrane dynamics for viral egress and dampen innate immune signaling; aminoacyl-tRNA and nucleotide sugar metabolism were enhanced to support viral protein synthesis and glycosylation. Notably, nucleotide metabolism was profoundly upregulated, with increased levels of adenosine, guanosine, adenine, and xanthosine. Transcriptomic validation (GSE8676 dataset) and qRT-PCR confirmed time-dependent upregulation of critical purine biosynthesis genes, including IMPDH, GMPS, ADSS2, GART, and ATIC, peaking at 48 hpi. These findings demonstrate that PRV orchestrates multifaceted metabolic takeover, with nucleotide metabolism emerging as a key vulnerability. Targeting this pathway may offer novel strategies to disrupt PRV replication, providing insights into viral-host metabolic crosstalk and antiviral development.